Encyclopedia of Inorganic and Bioinorganic Chemistry 2017
DOI: 10.1002/9781119951438.eibc2498
|View full text |Cite
|
Sign up to set email alerts
|

From3DIntermetallic Antiperovskites to2DHalf Antiperovskites

Abstract: The concept of ordered half antiperovskites (HAP) derives A 2 M 3 X 2 structures formally from metal‐rich intermetallic antiperovskites AM 3 X such as MgNi 3 C. It was developed within the last decade in Regensburg accompanied by fascinating discoveries of other groups. It extends the idea known for oxide structures related to perovskite such as cuprate superconductors: therein, the 3D M‐O ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 167 publications
0
6
0
4
Order By: Relevance
“…Der Cobalt-haltige Stempel der Presse hatte mit InS reagiert. [2,3,6] Die strukturellen Besonderheiten des Sn 2 Co 3 S 2 sind mit diesem Modell leicht zu verstehen. Letzteres hatte Ramdohr 1949 in Australien entdeckt, Shandit genannt und die hoch anisotrope trigonale Struktur (Raumgruppe R " 3m) bei gleichzeitig pseudo-kubischer Metrik beschrieben (siehe Lit.…”
Section: Wie Kerzen Im Christbaum Stehen Die Spins Ungepaarterunclassified
See 3 more Smart Citations
“…Der Cobalt-haltige Stempel der Presse hatte mit InS reagiert. [2,3,6] Die strukturellen Besonderheiten des Sn 2 Co 3 S 2 sind mit diesem Modell leicht zu verstehen. Letzteres hatte Ramdohr 1949 in Australien entdeckt, Shandit genannt und die hoch anisotrope trigonale Struktur (Raumgruppe R " 3m) bei gleichzeitig pseudo-kubischer Metrik beschrieben (siehe Lit.…”
Section: Wie Kerzen Im Christbaum Stehen Die Spins Ungepaarterunclassified
“…[6] Der GMR-Effekt bewies bereits,w ie aus Grundlagenforschung High-Tech-Anwendungen entstanden. Letztere finden sich auf einer Kurve entweder hoher Hall-Leitfähigkeiten bei niedrigen Hall-Winkeln (z.…”
Section: Wie Kerzen Im Christbaum Stehen Die Spins Ungepaarterunclassified
See 2 more Smart Citations
“…Sn 2 Co 3 S 2 was first prepared by Zabel et al in 1979, [5] when they found isotypic In 2 Co 3 S 2 from high pressure investigations on indium sulfide.T he stamp of the press contained cobalt and reacted with InS.Zabel and Range and co-workers found that both 2:3:2C oa nd the homologous nickel compounds crystallized in isotypic structures of the mineral Pb 2 Ni 3 S 2 .T he latter was discovered by Ramdohr in 1949 in Australia, who called it shandite and described already its highly anisotropic structure of space group R " 3m with pseudo cubic metrics. [2,6] ForSn 2 Co 3 S 2 this is visualized in Figure 1by its primitive Sn substructure that is centered by Sa toms. Significant bonding is however formed by Co atoms in half of the Sn 4 faces,that is,face-sharing S 2 Sn 4 polyhedra.…”
mentioning
confidence: 99%